Wariacje jazzowe w kinie "młodych gniewnych" - Śliwińska, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2009)
Jazz variations in “angry young men” cinema Jazz music and the vision of the world depicted by the “angry young men” are connected by a mysterious bond, its basis being not a simple citation of musical pieces, but functioning based on the identicalness of conveyed feelings and thoughts. Rarely can one find an example of correspondence of arts characterised by such extraordinary cohesion of thought and outlook on life. The objective of the present text is not to show the way jazz music functions in the “angry young men’s” films, but to take a closer look at this tangent point, this place where two worlds meet – worlds which are completely different, and yet, in consequence, alike. It transpires, after all, that there is only one way to self-cognition (whether in jazz or “angry young men’s” cinema) – the one leading through daring steps, rebellion and improvisation.